The RF and microwave handbook. - Golio, John Michael, 1954-; Golio, Janet (Electrical engineering handbook series., 2008)
This volume, RF and Microwave Applications and Systems, includes a wide range of articles that discuss RF and microwave systems used for communication and radar and heating applications. Commercial, avionics, medical, and military applications are addressed. An overview of commercial communications systems is provided. Past, current, and emerging cellular systems, navigation systems, and satellite-based systems are discussed. Specific voice and data commercial systems are investigated more thoroughly in individual chapters that follow. Detailed discussions of military electronics, avionics, an.